2011
DOI: 10.2485/jhtb.20.161
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal Bone Cyst of the Patella

Abstract: Aneurysmal bone cysts account for less than 1% of primary bone tumors and have a predilection for the metaphyses of the long bones of the leg. Only 1% of all aneurysmal bone cysts occur in the patella. We report on a 24-year-old man with a primary aneurysmal bone cyst in the left patella treated with curettage. The defect was filled with autogenic and allogeneic cancellous bone graft. The patient experienced no pain or tenderness and had a full range of knee movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The development of primary ABC in the patella is rare. An English literature review ( Table 1 ) 1 23 indicated that there were only 25 reported cases of primary ABC of the patella, including the present case, over the past 60 years.…”
Section: Discussionmentioning
confidence: 95%
“…The development of primary ABC in the patella is rare. An English literature review ( Table 1 ) 1 23 indicated that there were only 25 reported cases of primary ABC of the patella, including the present case, over the past 60 years.…”
Section: Discussionmentioning
confidence: 95%